Beneficial Application of Facilities Management In Hotel Organizations in South-Western Nigeria - Durodola, Olufemi Daniel; Ayedun, Caleb Abiodun; Adedoyin, Akinjare Omolade (Mediterranean Journal of Social Sciences, 2012)
A survey was conducted of probabilistically determined fifty-seven hotels of various ‘stars’ in South-Western geopoliticalzone of Nigeria to investigate the beneficial applications of Facilities Management (FM) in the hotel organizations. Datawere collected from hotel organizations through their general managers, staff and customers with the aid of questionnaires. Acombination of stratified and cluster sampling techniques were used. Kothari’s formula was adopted to determine the appropriatesample size while descriptive statistics, ranking and Spearman Correlation analysis were carried out. It was found that aboutthirteen benefits were common to all the stakeholders (Hotel organizations, Facilities Managers and Customers) while additionalfive benefits were just peculiar to the Facilities Managers and Customers only. Curiously, the flaunted benefit of FM asinstrument of strategic management by literature was not reckoned with, thus affirming that receptivity to FM is at low-ebb in thehotel sector of Nigeria’s economy and a pointer to ignorance of FM as instrument of strategic change. The study recommendedthat International Facilities Management Association (Nigeria Group), hotel organizations and Governments at all levels inNigeria should be conscious of this development and put in place strategic actions to market and educate the gentries on theefficacy of FM in running hotel businesses.